Comparative Analysis of Low-contrast Detectability (LCD) using a 4-AFC: Filtered Back Projection (FBP) and Iterative Reconstruction (IR) Images (International Journal of Scientific Research in Science and Technology, 2025)
Purpose: This study aims to evaluate low-contrast detectability (LCD) and investigate the effect of the filtered-back projection (FBP) and iterative reconstruction (IR) reconstruction algorithms on object size differences sing 4-alternative forced choice (4-AFC). Methods: Phantom images of the AAPM CT Performance Model 610 were scanned using GE Healthcare Revolution Evo 128 Slice CT scanner at 120 kV and 300 mA. Images are reconstructed using the FBP and IR 50%. A total of 6 radiographers served as observers in this study to assess low-contrast objects and small objects between 2.5 mm and 7.5 mm using the 4-AFC approach with a total of 440 questions. Results: It is found that the detection rate decreased for 3.5 mm objects with an overall decrease of 22% using FBP, and a decrease of 12% for 3.0 mm objects with IR. In terms of image reconstruction, IR out performed FBP with an 11% improvement in LCD. Conclusions: This study concludes that the 4-AFC method is effective for LCD on small objects. IR can be considered as a better image reconstruction approach to improve LCD, especially in small sized objects.